2015
DOI: 10.1007/s11906-015-0598-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Influencing Circadian Blood Pressure Patterns Among Individuals with HIV

Abstract: HIV+ individuals have an increased risk for cardiovascular disease (CVD), but the mechanisms behind this association are poorly understood. While hypertension is a well-established CVD risk factor, clinic-based blood pressure (BP) assessment by itself cannot identify several important BP patterns, including white coat hypertension, masked hypertension, nighttime hypertension, and nighttime BP dipping. These BP patterns can be identified over a 24-h period by ambulatory BP monitoring (ABPM). In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 84 publications
(76 reference statements)
0
23
0
Order By: Relevance
“…29, 30 Moreover, the significance of blood pressure rhythms in human disease is highlighted in human conditions where rhythms are absent, as in non-dipper hypertensive patients 31 that exhibit a raised incidence of cardiovascular morbidity. 32 Moreover, the prevalence of non-dipping blood pressure is not trivial, but may be up to 45% in humans 33 and may even further impact individuals with HIV 34 while targeting non-dipping blood pressure with night-time administration of antihypertensives may even be beneficial in diabetes. 35 …”
mentioning
confidence: 99%
“…29, 30 Moreover, the significance of blood pressure rhythms in human disease is highlighted in human conditions where rhythms are absent, as in non-dipper hypertensive patients 31 that exhibit a raised incidence of cardiovascular morbidity. 32 Moreover, the prevalence of non-dipping blood pressure is not trivial, but may be up to 45% in humans 33 and may even further impact individuals with HIV 34 while targeting non-dipping blood pressure with night-time administration of antihypertensives may even be beneficial in diabetes. 35 …”
mentioning
confidence: 99%
“…6 For example, infection with the virus disrupts normal circadian rhythms and has been associated with poor sleep quality and sleep disturbances, all factors that have been associated with non-dipping BP. 6, 15 HIV is associated with elevated systemic inflammatory biomarkers, which fail to fully return to normal levels with ART. 5, 6 Excess inflammation has been associated with masked hypertension and non-dipping BP in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…4 ABPM may be particularly useful for HIV+ adults, as this population has a high psychosocial burden, and a high prevalence of autonomic dysfunction and sleep disturbance. 6 Each of these are risk factors for ABPM phenotypes associated with high CVD risk, including nocturnal hypertension, a non-dipping BP pattern, and masked hypertension. 6 In a recent systematic review, only eight studies of ABPM in HIV+ adults were identified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations